2008
DOI: 10.1139/t08-044
|View full text |Cite
|
Sign up to set email alerts
|

Axial testing and numerical modeling of square shaft helical piles under compressive and tensile loading

Abstract: Helical piles are increasingly used to support and rehabilitate structures subjected to both tensile and compressive axial loads. This paper presents a detailed investigation into the axial performance of helical piles. The study encompasses 19 full-scale load tests in different soils and numerical modeling using finite element analysis. The ultimate load criteria and load transfer mechanisms for helical piles were examined. In addition, the relationship between the installation effort (torque) and pile capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(65 citation statements)
references
References 15 publications
1
53
0
1
Order By: Relevance
“…Sakr (2011) reported that uplift capacity of helical piles is about 80% of compressive capacity, but, Livneh and El Naggar (2008) had reported fewer values of uplift capacities. They proposed a failure criterion to predict the ultimate load for the helical piles.…”
Section: Background On Bearing Capacitymentioning
confidence: 99%
“…Sakr (2011) reported that uplift capacity of helical piles is about 80% of compressive capacity, but, Livneh and El Naggar (2008) had reported fewer values of uplift capacities. They proposed a failure criterion to predict the ultimate load for the helical piles.…”
Section: Background On Bearing Capacitymentioning
confidence: 99%
“…They proposed a failure criterion to predict the ultimate load for the helical piles. The ultimate load is defined as the load associated with deflection equal to 8% of the diameter of the largest helix plus the elastic deflection of the pile [17].…”
Section: Background On Bearing Capacitymentioning
confidence: 99%
“…3. a) Schematic of the FCV, b) Idealized distribution of stresses within control volume [17] to which it is pressurized. Sedran (1999) reported the factors relevant to FCV in his research [18].…”
Section: Physical Modeling For Studying Helical Pile Performancementioning
confidence: 99%
“…The screw piles were initially used primarily as anchors, and therefore focused on tensile loads such as transmission tower sand buried pipelines. However, their use has been extended to structures that are subject to compressive, tension and lateral loading [13]. The screw pile system is not suitable for the foundation in gravely or stiff soil, as the helix plates can be damaged during the process of pile installation.…”
Section: Introductionmentioning
confidence: 99%